The Usefulness of Molecular Markers Approach for Developing Heterotic Groups in Maize - Suwarno, Willy B (Journal of Tropical Crop Science, 2014)
The phenomenon of heterosis provides a greatopportunity for plant breeders to gain greaterperformance and yield in the hybrids compared to theirinbred line parents. In most cross-pollinated crops likemaize, heterosis plays an important role as theperformance of the hybrids is of a great value. Heterosisgain much interest until recently and current studies stillattempt to elucidateone of these is utilizing molecularmarkers to estimate genetic distances among inbredlines followed by developing putative groups. In a welldened heterotic group, between-groups mating areexpected to produce better hybrids than within-groupsmating. Some studies of marker-aided heterotic groupdevelopment resulted in functional heterotic groups;while some other reported that the groups failed toprovide evidence of heterosis in the hybrids.Considering the prediction of hybrids' performance willdepend on genetic background of inbred lines, andmarkers technology are continuously improved, there isstill a good opportunity to obtain useful heterotic groupsfor a particular breeding population.Keywords: maize breeding, genetic distance, heterosis,molecular markers.